RADEC LEARNING MODEL IN AN EFFORT TO IMPROVE CRITICAL THINKING SKILLS IN CITIZENSHIP EDUCATION LEARNING AT MUHAMMADIYAH SMP, SUMBANG - Ine Kusuma Aryani; Ristiana Dyah Purwandari; Eko Priyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine whether there is an increase in critical thinking skills in Civics learning by using the RADEC learning model. The type of research used is phenomenological qualitative research, the population in this study is 2 classes VIII A-B SMP Muhammadiyah, with the total number of students is 90 out of 3 classes. Data collection techniques in this study were carried out by using observation, interview and documentation techniques to determine critical thinking skills with 20 items of questions. (1) the RADEC learning model can improve students' critical thinking skills, (2) the Civics learning process using the RADEC learning model. This means whether the RADEC learning model is more appropriate to use in Civics learning to improve critical thinking skills in SMP Muhammadiyah Sumbang Class VIII. Keywords: RADEC learning model, critical thinking, Citizenship Education